Treatment of Induced Lead Toxicity by using DMSA in Puppies - Omar-Althani Shareef Saed1, S. M. A. AL-Kubaisi2, Jassim Mohamed Suleiman1, Mustafa Salah Hasan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
To determine efficacy of DMSA in treatment of sub-chronic lead exposure in dogs, fifteen puppies aged 2-4 months from both sexes were used for experimental induction of lead toxicity. These puppies were adapted for two weeks and divided randomly to three groups , each group contain five puppies; Group 1 which was regarded as negative control; Group 2, this group was drenched 15mg/kg of lead acetate daily for sixty days; Group 3, this group was drenched 15mg/kg of lead acetate daily for sixty days then were treated with DMSA 10 mg/Kg twice daily orally for one week. These animals were clinically examined daily till the end of experiment, then whole blood, bone, liver and brain were collected for estimation the lead concentrations. The results showed presence of several signs after 15 days of exposure which included depression, diarrhea, tremor then these signs subsides after 7 days of treatment with DMSA. Also, the results presented a significant increasing in the concentrations of lead in liver, blood, bone and brain in group 2 as compared with control group, after treatment with DMSA, group 3 showed a significant decrease in lead concentrations in liver , blood, bone, and brain as compared with group 2. In conclusion, DMSA is an effective therapy for clinical cases of lead toxicity.